Evaluasi Struktur Beton Bertulang Dengan Sistem Rangka Pemikul Momen Khusus Pada Gedung KORPRI Kab. Garut - Nugi Abdul Chalid; Eko Walujodjati (Jurnal Konstruksi, 2024)
To withstand earthquake forces in earthquake-prone areas, especially in seismic design categories 4,5,6 according to SNI 1726:2019, there is a calculation called the Special Moment Resisting Framing System (SRPMK). This research aims to understand the concept of earthquake-resistant buildings, plan reinforced concrete structures according to SRPMK principles, and determine the fulfillment of the Strong Column Weak Beam rule where columns are designed to be stronger than beams. The case study was carried out at the Garut Regency KORPRI building using the Garut Regency spectrum response. This building functions as the secretariat for the district KORPRI management board, as well as providing general administration services. The analysis is carried out by knowing the response spectrum, modeling, entering loads, and load combinations. The results of this research show that to fulfill the Special Moment Resisting Frame System in the KORPRI Garut Regency building, beams with dimensions of 350 x 500 mm and column dimensions of 400 x 400 mm are required and reinforcement is installed by the SRPMK provisions contained in SNI 2847:2019. This calculation also includes compliance with the Strong Column Weak Beam rule, this is related to the calculation of compliance with the SCWB formula in SNI 2847:2019